2019
DOI: 10.33594/000000140
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Mechanisms of Propolis Against CCl4-Mediated Liver Injury by Mediating Apoptosis of Activated Hepatic Stellate Cells and Improving the Hepatic Architecture through PI3K/AKT/mTOR, TGF-β/Smad2, Bcl2/BAX/P53 and iNOS Signaling Pathways

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 80 publications
4
8
0
Order By: Relevance
“…Supplementation of propolis is successfully recovered the changes induced by CCl 4 injection. 65 The present study showed decreases in Bcl-2 mRNA expres-…”
Section: Detection Of Caspase-9 and Bcl-2 In Liver And Kidney Tissuessupporting
confidence: 53%
“…Supplementation of propolis is successfully recovered the changes induced by CCl 4 injection. 65 The present study showed decreases in Bcl-2 mRNA expres-…”
Section: Detection Of Caspase-9 and Bcl-2 In Liver And Kidney Tissuessupporting
confidence: 53%
“…Nowadays, numerous functional foods and their ingredients are involved in the amelioration of the chemical's toxicity due to their antioxidant and anti-inflammatory roles 13 17 , 18 . Acacia Senegal (AS) gum (Gum Arabic), which is a naturally occurring exudate derived from the trunk and branches of AS and Acacia seyal trees, is one of these functional foods that have numerous medicinal effects.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we related effects of EGCG to signalling pathways of AKT and mTOR as an index to HSCs activations. 20 Assessing these pathways were performed through western blot analysis by choosing ECGC with the concentration of 50 µM. Online supplemental figure 3B, C showed less phosphorylated AKT and mTOR in the LX2 NTCP+ cells following incubations with the EGCG.…”
Section: Resultsmentioning
confidence: 99%